2012
DOI: 10.1111/cob.12004
|View full text |Cite
|
Sign up to set email alerts
|

Socio‐demographic and obstetrical correlates of pre‐pregnancy body mass index and gestational weight gain

Abstract: Both pre-pregnancy body mass index (BMI) and gestational weight gain (GWG) are important determinants of a healthy pregnancy outcome and may show important variation. To study the influence of socio-demographic and obstetrical correlates on pre-pregnancy BMI and GWG, data of 54 022 singleton term pregnancies were analysed using adjusted regression models. In 2009, in the Northern region of Belgium, one-third of women were overweight (21.6%) or obese (10.1%) and GWG as recommended by the Institute of Medicine o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 42 publications
5
41
0
Order By: Relevance
“…Numerous studies explored more diverse racial/ethnic groups (Neser, 1963; Allen et al., 1994; Frisbie, Forbes & Hummer, 1998; Larouche et al., 2010; Bogaerts et al., 2012; Kowal, Kuk & Tamim, 2012; Gaillard et al., 2013; Hernandez-Rivas et al., 2013; Sommer et al., 2014; Bahadoer et al., 2015; Deputy et al., 2015; Kinnunen et al., 2016) but there were too few similarities within the data to compare GWG patterns. These studies are included in the summaries presented in Table 2 (2009 IOM guidelines).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies explored more diverse racial/ethnic groups (Neser, 1963; Allen et al., 1994; Frisbie, Forbes & Hummer, 1998; Larouche et al., 2010; Bogaerts et al., 2012; Kowal, Kuk & Tamim, 2012; Gaillard et al., 2013; Hernandez-Rivas et al., 2013; Sommer et al., 2014; Bahadoer et al., 2015; Deputy et al., 2015; Kinnunen et al., 2016) but there were too few similarities within the data to compare GWG patterns. These studies are included in the summaries presented in Table 2 (2009 IOM guidelines).…”
Section: Resultsmentioning
confidence: 99%
“…24 Concurrently, a high postpartum weight retention is an important contributor to long-term maternal obesity. More specifically, the increased risk for GDM and pregnancy-induced hypertension was only present in underweight and normal-weight women.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from Belgium, Canada and Sweden demonstrated an inverse association (but the association only being apparent in those with healthy pre-pregnancy weight in the Swedish study) [49][50][51], while nine studies from Iran, USA, Australia/New Zealand, Brazil and the Netherlands found no association [52][53][54][55][56][57][58][59][60]. One study from New York found that the relationship was complex and depended upon area of residence [61].…”
Section: High Maternal Weight Gain In Pregnancymentioning
confidence: 99%